Management Education: Strategies for Strengthening Hajj and Umrah Businesses at an Early Age at Majelis Taklim Al-Usmaniyah, Rawa Gempol, Teluk Naga, Tangerang Regency - Kiki Dian Angraeni; Ahmad Jalaludin (IRDH International Journal of Social Sciences & Humanities, 2025)
The goal is to provide management education and strategies for strengthening the Hajj and Umrah business to the community, especially the younger generation, from an early age. The method of implementing the activity includes the presentation of material on the concept of Sharia-based Hajj and Umrah business management, interactive discussions, simulations of preparing simple business plans, and evaluation of participant understanding. The seminar participants numbered 60 people, consisting of teenagers, housewives, and community leaders. This activity is designed not only to increase knowledge, but also to motivate participants to be able to take advantage of business opportunities in the field of religious travel services professionally. The evaluation results showed a significant increase in participant understanding. As many as 85% of participants said they had a better understanding of the basic concepts of Hajj and Umrah business management, and 70% of them expressed interest in starting a business in this sector. Participants were also able to prepare a simple business plan that includes opportunity analysis, cost estimates, and marketing strategies. This activity proves that early childhood development is important to prepare a generation of Hajj and Umrah business actors who are competent, have integrity, and comply with Sharia principles. In the future, it is hoped that there will be follow-up programs in the form of digital marketing training, Sharia financial management, and strengthening business networks so that this potential can develop sustainably.